2023
DOI: 10.1002/adfm.202311465
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Coating of Ionic Diode Arrays Toward Flexible Moist‐Electric Generators to Power Wireless Sensor Nodes

Yuming Yao,
Xulei Lu,
Chunqiao Fu
et al.

Abstract: Ubiquitous moisture is attractive for developing sustainable mobile power sources. However, how to endow moisture‐electric generators (MEGs) with fine design, mass customization, high power output, and foldability is still a largely unsolved problem. In this work, based on the Patterned Coating method, use is made of modulated carbon nanotube, nano‐Al2O3, and liquid metal inks to design and fabricate MEGs with properties required for their applications. A single MEG of the ionic diode type thus fabricated can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Wang et al used stacking to raise the voltage of the arrayed devices to 1000 V (figures 11(c) and (d)), while combining supercapacitors to charge lithium batteries and light high-power light bulbs [15]. Based on a simple patterned coating method, Yao et al realized a short-circuit current with an integrated device up to 1.95 mA (figures 11(e) and (f)) [81]. Copyright (2020), with permission from Elsevier.…”
Section: Power Supplymentioning
confidence: 99%
“…Wang et al used stacking to raise the voltage of the arrayed devices to 1000 V (figures 11(c) and (d)), while combining supercapacitors to charge lithium batteries and light high-power light bulbs [15]. Based on a simple patterned coating method, Yao et al realized a short-circuit current with an integrated device up to 1.95 mA (figures 11(e) and (f)) [81]. Copyright (2020), with permission from Elsevier.…”
Section: Power Supplymentioning
confidence: 99%
“…Electrical heating textiles could provide active thermal management with reliable temperature control and are widely used in outdoor sports to adapt to climate change, such as hiking, fishing, and skiing. Electrical heating fabrics need to take into account several characteristics, including engendering heat with a mobile power supply, remaining breathable to transmit moisture, and keeping flexible for wearability, which has aroused significant interest among researchers. The design and fabrication of electrical heating fabrics could be classified into two kinds: conductive fiber-based fabrics and surface-modified fabrics with a conductive dopant. The first kind generally employed conductive polymers (e.g., polythiophene, polyaniline, and polypyrrole) to fabricate conductive fibers with different spinning technologies, including wet spinning, thermal drawing, and microfluidic blown spinning. , And the conductive fibers were woven into fabrics, which showed great flexibility and wearability.…”
Section: Introductionmentioning
confidence: 99%
“…3–6 Similar to biological systems, the energy coupling and signal transmission mechanisms in HPGs are intricately linked to selective ion/molecule transport. 7–10 In 2017, Guo et al reported the inaugural work using the interactions between water molecules and a porous carbon-black film for HPGs, achieving a sustained open-circuit voltage ( V oc ) of 1 V and a short-circuit current density ( I sc ) of 60 nA cm −2 . 11 With consistent capillary infiltration of water within the surface-charged micro-scaled pores/channels, an electrical double layer is developed at the water–solid interface, enabling selective separation and oriented transport of charges by the Debye screening effect.…”
Section: Introductionmentioning
confidence: 99%